Arabidopsis Plants Sense Non-self Peptides to Promote Resistance Against Plectosphaerella cucumerina - Pastor-Fernández, Julia; Gamir, Jordi; Pastor, Victoria; Sanchez-Bel, Paloma; Sanmartín, Neus; Cerezo, Miguel; Flors, Víctor (Frontiers in Plant Science, 2020)
Peptides are important regulators that participate in the modulation of almost every physiological event in plants, including defense. Recently, many of these peptides have been described as defense elicitors, termed phytocytokines, that are released upon pest or pathogen attack, triggering an amplification of plant defenses. However, little is known about peptides sensing and inducing resistance activities in heterologous plants. In the present study, exogenous peptides from solanaceous species, Systemins and HypSys, are sensed and induce resistance to the necrotrophic fungus Plectosphaerella cucumerina in the taxonomically distant species Arabidopsis thaliana. Surprisingly, other peptides from closer taxonomic clades have very little or no effect on plant protection. In vitro bioassays showed that the studied peptides do not have direct antifungal activities, suggesting that they protect the plant through the promotion of the plant immune system. Interestingly, tomato Systemin was able to induce resistance at very low concentrations (0.1 and 1 nM) and displays a maximum threshold being ineffective above at higher concentrations. Here, we show evidence of the possible involvement of the JA-signaling pathway in the Systemin-Induced Resistance (Sys-IR) in Arabidopsis. Additionally, Systemin treated plants display enhanced BAK1 and BIK1 gene expression following infection as well as increased production of ROS after PAMP treatment suggesting that Systemin sensitizes Arabidopsis perception to pathogens and PAMPs.